2013
DOI: 10.1039/c3an01137b
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a protease sensor for caspase-3 activity detection based on surface plasmon resonance

Abstract: Diagnosis of apoptosis is essential to the early detection of therapy efficiency and the evaluation of disease progression. Caspase-3 is supposed to be closely related to cellular apoptosis. We describe here a label-free surface plasmon resonance (SPR) detection of apoptosis based on caspase-3 activity assay through enzyme digestion. An artificial peptide sequence was designed as a substrate of caspase-3 and immobilized on a gold disk through covalent binding. The 4Lys part at the end of the pentadecyl-peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…The ratios of reactive volumes between Fe 3 O 4 and HAuCl 4 solution were 1:2. Stirring continued for 10 min after the color change ceased [25]. The solution was cooled to room temperature with a continuous stirring for another 45 min.…”
Section: The Gmps Synthesis and Immobilization Of Apt2 Onto Gmpsmentioning
confidence: 99%
“…The ratios of reactive volumes between Fe 3 O 4 and HAuCl 4 solution were 1:2. Stirring continued for 10 min after the color change ceased [25]. The solution was cooled to room temperature with a continuous stirring for another 45 min.…”
Section: The Gmps Synthesis and Immobilization Of Apt2 Onto Gmpsmentioning
confidence: 99%
“…Additionally, these photometric approaches are confronted with insufficient sensitivity due to the technical limitation of themselves. Our group have reported a novel caspase-3 sensor with excellent sensitivity by using surface plasmon resonance (SPR) technique (Chen et al, 2013). However, it still has problems in terms of the cost of equipment and specially trained operator.…”
Section: Introductionmentioning
confidence: 99%
“…Upon cleavage of the ferrocene-conjugated DEVD peptide, a decrease in ferrocene oxidation signal denoted caspase-3 activity in assay samples. Recently, Chen et al [24] reported the development of a caspase-3 sensor using surface plasmon resonance in connection with EIS. In their study, a pentadecylpeptide containing the caspase-3 specific peptide motif, DEVD, was covalently immobilized on Au surface using a cysteine placed at the C-terminus of the peptide sequence.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that a 15-min incubation period with caspase-3 was sufficient for their procedure. However, the effect of non-specific adsorption or sensitivity issues in complex matrices such as cell lysates were not discussed [24].…”
Section: Introductionmentioning
confidence: 99%